Evidence of spin and charge density waves in Chromium electronic bands - Federico Bisti; Paolo Settembri; Jan Minár; Victor A. Rogalev; Roland Widmer; Oliver Gröning; Ming Shi; Thorsten Schmitt; Gianni Profeta; Vladimir N. Strocov (Communications Materials)
Abstract The incommensurate spin density wave (SDW) of Chromium represents the classic example of itinerant antiferromagnetism induced by the nesting of the Fermi surface, which is further enriched by the co-presence of a charge density wave (CDW). Here, we explore its electronic band structure using soft-X-ray angle-resolved photoemission spectroscopy (ARPES) for a proper bulk-sensitive investigation. We find that the long-range magnetic order gives rise to a very rich ARPES signal, which can only be interpreted with a proper first-principles description of the SDW and CDW, combined with a band unfolding procedure, reaching a remarkable agreement with experiments. Additional features of the SDW order are obscured by superimposed effects related to the photoemission process, which, unexpectedly, are not predicted by the free-electron model for the final states. We demonstrate that, even for excitation photon energies up to 1 keV, a multiple scattering description of the photoemission final states is required.